Effectiveness of a Problem-Based Learning Model with Quizizz Learning Media on Science Learning Outcomes - Denis Novitasari; Isa Ansori; Arif Widagdo (Postgraduate, University of Mataram, 2023)
This study was motivated by the low learning outcomes of grade 5th students at Elementary School 14 Sragen in science subjects due to suboptimal learning. The purpose of this study was to test the effectiveness of the Problem-Based Learning learning model with Quizizz media on the science learning outcomes of fifth grade students of Elementary School 14 Sragen. This type of research is experimental research with a quasi-experimental research design. The research method used is Quasi-experimental design, research sampling involves two study groups of grade V students, namely the experimental class and the control class, with a total of 17 students each. The data analysis method was carried out by applying a paired sample t-test to test the hypothesis and N-gain test to assess the effectiveness of the learning model. The results showed that PBL with Quizizz media was declared effective based on the paired sample t-test with a result of 0.000, which means that there is an average difference in student science learning outcomes between the problem-based learning model with Quizizz media and the STAD model. The experimental class N-gain test results were higher than the control class 79.2532> 53.8574 effective criteria. Based on the results of the study, it shows that the application of the Problem-Based Learning learning model with Quizizz media can improve student learning outcomes and more effectively improve student science learning outcomes.